Hygienic coatings with nano-functionalized diatomaceous earth by Equisetum giganteum – Mediated green synthesis - Barberia Roque, Leyanet (2023)
Background: Microbiological growth on indoor surfaces has a negative impact on human health. Antimicrobial materials are intensely studied to prevent biodeterioration in an indoor environment. The present work seeks the green synthesis of an eco-friendly and cheap antimicrobial nano-functionalized filler from diatomaceous earth to be applied to the formulation of paints. Methods: Adsorption of silver ions and a green synthesis with Equisetum giganteum L. aqueous extract of nano functionalized diatomaceous earth was carried out. The nano-functionalized fillers were characterized by four ier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron micro scopy (TEM) and energy dispersive spectrometry (EDS). The antimicrobial activity was also assessed. Waterborne paints were formulated and prepared, then bioassays were performed to assess their antimicrobial efficiency. Significant findings: For the first time E. giganteum aqueous extract has been employed for the nano functionalization of diatomaceous earth (DE). Functionalized DE has the potential to prevent biodeterioration with 25 mg of silver per 100 g of paint, which has resulted in an eco-friendly alternative for hygienic coatings.